2022
DOI: 10.3389/fphar.2022.1057571
|View full text |Cite
|
Sign up to set email alerts
|

An intravenous anesthetic drug-propofol, influences the biological characteristics of malignant tumors and reshapes the tumor microenvironment: A narrative literature review

Abstract: Malignant tumors are the second leading cause of death worldwide. This is a public health concern that negatively impacts human health and poses a threat to the safety of life. Although there are several treatment approaches for malignant tumors, surgical resection remains the primary and direct treatment for malignant solid tumors. Anesthesia is an integral part of the operation process. Different anesthesia techniques and drugs have different effects on the operation and the postoperative prognosis. Propofol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 137 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…It has already been shown that incubation of colon carcinoma cells with sera from colon carcinoma patients who received Propofol anesthesia increased the apoptosis rate compared to Sevoflurane anesthesia [25], which indicates that serum factors are regulated using anesthetics and these might influence tumor growth, with a particular focus on EVs and associated miRNAs [35]. Propofol was shown to exhibit antitumor effects by regulating different miRNAs and lncRNAs and thus influencing important signaling pathways of carcinogenesis [36]. Moreover, Propofol inhibits proliferation, migration and invasion of bladder carcinoma cells through increased micro-RNA expression in vitro, being in line with our results [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been shown that incubation of colon carcinoma cells with sera from colon carcinoma patients who received Propofol anesthesia increased the apoptosis rate compared to Sevoflurane anesthesia [25], which indicates that serum factors are regulated using anesthetics and these might influence tumor growth, with a particular focus on EVs and associated miRNAs [35]. Propofol was shown to exhibit antitumor effects by regulating different miRNAs and lncRNAs and thus influencing important signaling pathways of carcinogenesis [36]. Moreover, Propofol inhibits proliferation, migration and invasion of bladder carcinoma cells through increased micro-RNA expression in vitro, being in line with our results [24].…”
Section: Discussionmentioning
confidence: 99%
“…If the choice of anesthesia affects tumor-inhibitory signaling pathways in patients that could prevent the development of metastases and recurrences via EVs and associated miRNAs, this possible therapeutic potential should be exploited and explored further. EVs themselves are already being explored as potential drug delivery vehicles for cancer therapy [48,49] while Propofol is under investigation as a chemosensitizer [36]. If Propofol was demonstrated to result in EV-modulated tumor inhibition in the surgical setting, this would be a simple and desirable way to improve patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have demonstrated that in addition to the sedative hypnotic effect, Propofol also affects the development of tumors, reduces the spread of cancer cells by regulating a variety of signaling pathways, and has direct anti-tumor effects[23; 37; 39]. Propofol was also reported that possessed a protective effect on systemic inflammation and immune function[39]. A multi-center retrospective clinical analysis has suggested that Propofol significantly extends survival after surgery for primary breast cancer compared to sevoflurane anesthesia, which may be related to its ability to reduce the function of breast cancer stem cells, induce apoptosis of breast cancer cells, and inhibit the proliferation of breast cancer cells[8].…”
Section: Introductionmentioning
confidence: 99%